Applications of silica-based nanoparticles for multimodal bioimaging. Issue 5 (28th May 2018) - Zheng, Xiaoke; Zeng, Shuli; Hu, Jing; Wu, Lan; Hou, Xiandeng
ABSTRACT: Multimodal imaging, as an important approach to circumvent the limitations of single imaging modality, has attracted extensive attention in recent years. With the rapid development of nanotechnology and the ongoing efforts to improve their targeting capability and endow multiple imaging ability, nanoprobes are expected to play crucial roles in multimodal imaging through integrating different imaging moieties or molecules into a single nanoparticle, where silica has been used intensively as a carrier or a medium for the construction of the nanoprobes due to its preferable characteristics including good biocompatibility, long blood circulation time, and ease of modification. Based on the types of the silica used for the fabrication of nanoprobes, solid silica-based and mesoporous silica-based nanoparticles were developed for multimodal imaging. Herein, the newly developed silica-based nanoparticles as multimodal imaging agents for disease diagnosis and therapy in the last 5 years were summarized, along with their fabrication process, specific applications, and especially the role of the silica.